Stages and directions of improvement of the regulatory framework of the simplified accounting and reporting system in Russia - T. P. Saraldaeva (Вестник университета)
The article considers the stages and characteristics of the modern system of regulatory regulation and the use of simplified methods of accounting and reporting in Russia. The paper outlines the circle of economic entities, that have the right to use them. The author carries out the classification of existing simplified methods, as well as presents the criteria for their application by organizations. The study gives a recommendation for the preparation of a single national standard for the use of simplified methods of accounting and accounting reporting. The paper considers and systematizes the regulatory legal acts, recommendations of the regulatory state body and accounting associations, as well as other documents related to the application and use of simplified accounting methods in Russia. For each of these documents, the author gives a brief analysis of the key provisions on the use of simplified methods.